RANCANG BANGUN MEDIA PEMBELAJARAN BERBASIS DIGITAL MATA PELAJARAN ILMU PENGETAHUAN ALAM KELAS V SEKOLAH DASAR - Marzuki, Marzuki (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
This study aims to build a digital learning platform as an alternative to learning, especially for science subjects. In addition, science subjects are one of the subjects included in the National Examination in Elementary Schools (SD) so that the deepening of this material is needed to prepare students. The research method used in this research method is the SDLC method which has stages, namely the identification stage, system requirements analysis stage, design stage and implementation stage and using UML tools when designing applications with built diagrams are different activities for students, teachers and admins. use case diagrams of students, teachers and admins. And a class diagram consisting of: admin table, student table, teacher table, class table, material table, assignment table, question table and grades table. Based on the results of the study, it can be concluded that this Natural Sciences (IPA) E-learning learning method can provide convenience for students to study at home which can be done anywhere and anytime, with various materials and tests or exams to hone skills in various references. that has been provided in the E-learning method.